1990
DOI: 10.1161/01.cir.82.5.1754
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of low molecular weight heparin by polybrene prevents thromboxane release and severe pulmonary hypertension in awake sheep.

Abstract: Protamine reversal of heparin anticoagulation in patients is occasionally associated with life-threatening acute pulmonary hypertension. In a sheep model, we evaluated the effect on this adverse cardiopulmonary reaction of modifying the type of heparin (low molecular weight heparin compared with unfractionated heparin) and the type of heparin antagonist (polybrene compared with protamine). Protamine reversal of low molecular weight heparin (LMWI) and polybrene reversal of unfractionated heparin induced more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 43 publications
0
23
0
1
Order By: Relevance
“…To assess whether FXIa inhibition by SPGG2 can be reversed, we studied protamine, polybrene and SOS. Protamine is a clinically used arginine-rich polypeptide that counteracts the anticoagulant activity of UFH and LMWHs [29], whereas polybrene is a quaternary amine-containing hydrophobic polymer, which has been explored as a probe of electrostatic interactions [30]. SOS is an FDA approved antacid that is known to bind in heparin-binding sites on proteins such as thrombin [31].…”
Section: Resultsmentioning
confidence: 99%
“…To assess whether FXIa inhibition by SPGG2 can be reversed, we studied protamine, polybrene and SOS. Protamine is a clinically used arginine-rich polypeptide that counteracts the anticoagulant activity of UFH and LMWHs [29], whereas polybrene is a quaternary amine-containing hydrophobic polymer, which has been explored as a probe of electrostatic interactions [30]. SOS is an FDA approved antacid that is known to bind in heparin-binding sites on proteins such as thrombin [31].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, thromboxane release into plasma was similar when heparinprotamine challenges were repeated at 90-minute intervals ( Figure 6) as reported in another study from our laboratory demonstrating that the course and magnitude of plasma thromboxane increase and pulmonary hypertension were not altered when heparinprotamine challenges were repeated at short-term intervals. 18 Fehr and Rohr,28 who demonstrated that administration of cobra venom factor to rabbits, associated with depletion of complement, prevented leukopenia during subsequent heparin-protamine challenges. Thus, although complement activation and pulmonary leukosequestration are consistent events during the heparin-protamine reaction, they do not appear to play a direct role in producing pulmonary vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…There is already significant concern with the continued use of protamine for reversal of systemic heparinization (40-43). Protamine reactions include hypotension and vascular collapse (12), as well as effects on hematologic and pulmonary function (40, 41,43,44). Our study might add the potential for exacerbation of proliferative vascular disease to this list.…”
Section: Methodsmentioning
confidence: 97%